The demon of politics.
1 online resource (280 pages).
Keywords: Mario Tronti is considered one of the most important Italian Marxist philosophers of our time, as well as one of the most influential European political theorists of the post-war period. Largely untranslated and hence unknown in the anglophone world, this is the second volume of a two-volume translation, The Demon of Politics, presenting an invaluable picture of Tronti's political life and intellectual activity through a selection of his most relevant writings.Volume II paints a fascinating picture of Tronti's work in the 1980s, 1990s, and 2000s, through his engagement with the traditions of political realism, 'negative thinking', and political theology. Essays herein also tackle the legacy of the 20th century from the angle of an intense reflection on the relations between history and politics. An introduction written by the editors contextualises Tronti's writings during the second part of his career, while also providing the biographical and political details necessary to understand the evolution of his thought in the later years. Footnotes throughout the volume provide valuable precisions and elements of contextualisation throughout the whole volume.The volumes of The Demon of Politics offer the most comprehensive edition of Tronti's works available to students and scholars.